PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENGANGKATAN CALON KEPALA SEKOLAH NEGERI BANDAR LAMPUNG DENGAN METODE SAW - Rirongga, Aron Naldi; Lestari, Sri (IIB Darmajaya, 2012)
The progress of a school cannot be separated from the influence of how the ability of school principals in managing all the resources that exist in the school. Therefore we need qualified human resources in this case the teachers who have the potential and achievements of the school in order to become the head of a quality education can be realized. Until now the appointment of principals in both primary and secondary schools is based on an assessment for someone serving as a teacher. These procedures contain serious flaws. Decision Support System is a system that can help the Department of Education of Bandar Lampung in decisions determining the appropriate teachers for the office of State High School principal and improve the quality of the resulting decision of selection committee. The method used in the manufacture of this website is SAW (Simple Additive Weighting), System Development Life Cycle (SDLC) Waterfall models. Data was collected through observation and literature while the implementation of the waterfall model is described through system analysis, DFD, database table structure, and design input output. To design and create a website using Macromedia Dreamweaver MX , PHP programming language, MySQL database, and web server xampp.Keywords: SAW (Simple Additive Weighting), the Head of School